The opportunities for criminal cooperation between the investigative authority of the National Tax and Customs Administration and the Southeast European Law Enforcement Center based on working experiences and best practices (Belügyi Szemle, 2025)
Aim: The Southeast European Law Enforcement Center (hereinafter: SELEC) is a centre for criminal cooperation between police forces and customs services of the Balkan and other neighbouring countries, including Hungary, primarily for the prevention and combating of serious and organised crime that may have a cross-border element or that is actually or presumably cross-border in nature. The main objective of the present study is to identify and isolate the main potential factors that could serve as motives for the National Tax and Customs Administration's Directorate General of Criminal Investigation (hereinafter: NTCA investigative authority) in its international criminal cooperation with the SELEC.Methodology: Following the analysis of the secondary literature and the knowledge base of the good practice and work experience observed in the above-mentioned organisations, the main motivational factors corresponding to the study objectives were identified, isolated and further considered.Findings: based on secondary research and the knowledge base of observed good practice and work experience, three factors - namely speed, accuracy and cost-effectiveness of information exchange - can be identified as the main motives for criminal cooperation between the NTCA investigative authority and the SELEC.Value: If the findings of this study are accepted, it can be concluded that speed, accuracy and cost-effectiveness of information exchange may be the three main factors that motivate criminal cooperation between the NTCA investigative authority and the SELEC. Further reflection on the findings may suggest that the use of the Law Enforcement Centre's information channels may further assist in supporting both the strategic objectives of the NTCA investigative authority in particular. In order to take full advantage of the above, and particularly given the flexibility and efficiency of informal liaison, it would be worth considering the delegation of a permanent SELEC liaison officer from the NTCA Investigative Authority.